2017
DOI: 10.1016/j.ijdevneu.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum Neuron‐specific enolase, S100B, myelin basic protein and glial fibrilliary acidic protein as brain specific proteins in children with autism spectrum disorder

Abstract: While serum NSE, MBP, and S100B values cannot be considered as biomarkers for ASD, GFAP may be a biomarker and is suggested as a possible indicator of autism severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 60 publications
1
38
1
Order By: Relevance
“…A study, including 40 children with autism reported not only their increased S100B concentrations, but its association with autism severity (Guloksuz et al 2017). Contrary, one study with 35 children with ASD found no difference in serum S100B with controls (Esnafoglu et al 2017). This discordance in results could be based on small groups of included children, amongst which our study was the largest.…”
Section: Discussioncontrasting
confidence: 89%
“…A study, including 40 children with autism reported not only their increased S100B concentrations, but its association with autism severity (Guloksuz et al 2017). Contrary, one study with 35 children with ASD found no difference in serum S100B with controls (Esnafoglu et al 2017). This discordance in results could be based on small groups of included children, amongst which our study was the largest.…”
Section: Discussioncontrasting
confidence: 89%
“…Astrocyte‐derived membranous blebs have not been observed in other CNS disorders, and we suggest they may be generated by a targeted attack of astrocyte processes by cytotoxic T lymphocytes specifically at the glia limitans surrounding blood vessels and other CFS–brain boundaries. Consistent with our findings of increased GFAP + astrocyte debris in perivascular Virchow–Robin space CSF in ASD, GFAP is elevated in CSF and serum in a large proportion of individuals with ASD . The strong separation of ASD from control cases on a lymphocyte count versus jaggedness index scatterplot (see Fig D) and the correlation of lymphocyte count with astrocyte debris on a scatterplot of ASD cases (see Fig C) suggest these histologic features could be causally connected biomarkers of the ASD pathogenic process.…”
Section: Discussionmentioning
confidence: 61%
“…Consistent with our findings of increased GFAP + astrocyte debris in perivascular Virchow-Robin space CSF in ASD, GFAP is elevated in CSF and serum in a large proportion of individuals with ASD. 13 The strong separation of ASD from control cases on a lymphocyte count versus jaggedness index scatterplot (see Fig 5D) and the correlation of lymphocyte count with astrocyte debris on a scatterplot of ASD cases (see Fig 2C) suggest these histologic features could be causally connected biomarkers of the ASD pathogenic process. Our findings suggest future diagnostic evaluations and research of ASD postmortem brains should examine the following: (1) perivascular CD8 + T-lymphocyte infiltrates, (2) CSF-glia limitans barrier damage (including increased perivascular space and collagen deposition), and (3) GFAP + astrocyte membranous blebs in CSF space compartments.…”
Section: Discussionmentioning
confidence: 95%
“…The evidence for whether BBB disruption is present in ASD based on molecular markers of increased BBB permeability such as S100B, GFAP, neuron-specific enolase (NSE), myelin basic protein (MBP), and creatine kinase brain isoenzyme (CK-BB) is mixed. One recent study found that S100B, GFAP, and NSE did not differ between ASD and control children but did find that GFAP levels were significantly higher in ASD individuals and GFAP levels positively correlated with scores on the Childhood Autism Rating Scale [147]. Other studies did find significantly increased levels of S100β in serum [148] and in plasma [149] for children with ASD and that this correlated with increased levels of the cytokine tumour necrosis factor-alpha (TNF-α) [149].…”
Section: Markers Of Bbb Permeability In Asdmentioning
confidence: 99%